The effect of titania content on the physical properties of polyimide/titania nanohybrid films - DUMLUDAĞ, FATİH; KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (WILEY-BLACKWELL, 2012)
In this study, a series of PI/TiO2 nanohybrid materials were prepared from polyamic acid of 3,3',4,4'-benzophenonetetracarboxylic dianhydride/3,3'-diaminodiphenyl sulfone, and titania precursor by the sol-gel method. The titania content in the hybrid system was varied from 0 to 5 wt %. The physical and mechanical properties of the hybrids such as refractive index, optical transmission, and tensile strength were investigated. It was determined that incorporation of titania precursor into the PI matrix improved the refractive indices and tensile modulus of the hybrid films. It was observed that the optical transmittance and tensile strength of the nanohybrids were slightly decreased with the increasing titania content. It was determined that the hybrid films might have enhanced the UV shielding properties compare to the PI films. Furhermore, the hybrid materials showed better thermal stability than the PI. SEM studies demonstrated that titania particles (1 and 3 wt %) were distributed homogeneously through the PI matrix. The effect of the titania content in the PI on DC conductivity and dielectric constant were also analyzed. For the PI film containing 5 wt % titania, activation energy value increased to 1.0 eV from the value of 0.65 eV. DC conductivity value of the films depending on titania content varied between 3.0 x 10(-11) and 1.4 x 10(-10) S/cm at room temperature. Relative dielectric constants of the films were calculated from capacitance measurements depending on frequency (40100 kHz) at different temperatures (303-360 K). The values increased with the increasing titania content. (C) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: nanocomposites; polyimides; thin films; dielectric properties; activation energy; HIGH REFRACTIVE-INDEX; NANO HYBRID FILMS; SOL-GEL PROCESS; DIELECTRIC-PROPERTIES; MECHANICAL-PROPERTIES; NANOCOMPOSITE FILMS; THIN-FILM; COATINGS; COMPOSITES; MORPHOLOGY